Effect of pH on competence development and deoxyribonucleic acid uptake in Streptococcus sanguis (Wicky). - Ranhand, J M (1976)
Streptococcus sanguis (Wicky) cells, strain WE4, developed little or no competence and failed to autolyze in permissive conditions when treated with competence factor (CF) below PH 7.0. This lack of activity was directly correlated with the inability of the cells to bind or take up CF at pH values of 5.5, 6.0, and 6.5. On the other hand, competent cells bound deoxyribonucleic acid molecules maximally below pH 7.0 and transformed maximally at pH 6.5. Deoxyribonucleic acid was optimally bound to cells in a deoxyribonuclease-resistant form at pH values between 7.0 and 8.5. Concomitant with this binding, undefined acid-soluble DNA fragments appeared in the culture menstrua. CF binding and uptake by cells was not only influenced by low pH but also by low temperature. At 0 C, WE4 cells bound only 4% of the input CF and took up less than 1% into a trypsin-insensitive state compared to cells treated at 37 C. Cells treated with CF at 0 C did not autolyze when transferred to permissive conditions. The results presented in this report extend earlier findings that showed that competence development and autolysis are related to the uptake of CF.